UPLC‐PDA‐TOF/MS coupled with multivariate statistical analysis to rapidly analyze and evaluate Ginkgo biloba leaves from different origin. Issue 3 (10th May 2013) - Yao, Xin; Zhou, Guisheng; Tang, Yuping; Guo, Sheng; Qian, Yefei; Jin, Chun; Qin, Yong; Qian, Dawei; Duan, Jin‐ao
<x xml:space="preserve">Abstract</x> In the present study, an ultra performance liquid chromatography coupled with photodiode array detector and time‐of‐flight mass spectrometry (UPLC‐PDA‐TOF/MS) was proposed and validated for rapidly analyzing and evaluating Ginkgo biloba leaves from different origins by using multivariate statistical analysis. Batches of these kinds of G. biloba leaves were subjected to UPLC‐PDA‐TOF/MS analysis, the datasets of retention time (RT)‐m/z pairs, ion intensities and sample codes were further processed with orthogonal partial least squared discriminant analysis (OPLS‐DA) to holistically compare the difference between these G. biloba leaves, and to generate an S‐plot. Those compounds correlated to the points at the two ends of S were regarded as the most differentiating components. By comparing the mass/UV spectra and retention times with those of reference compounds and/or tentatively assigned by matching empirical molecular formulae with those of the known compounds published in the literatures, these differentiating components were finally characterized as kaempferol 3‐O‐[2‐O‐(6‐O‐p‐hydroxy‐trans‐cinnamoyl)‐β‐D‐glucosyl)‐α‐L‐rhamnoside], kaempferol 3‐O‐[2‐O, 6‐O‐bis(α‐L‐rhamnosyl)‐β‐D‐glucoside], ginkgolide C, kaempferol 3‐O‐[2‐O‐(β‐D‐glucosyl)‐α‐L‐rhamnoside], and bilobetin. These compounds would be the potential chemical markers for the two kinds of leaves. The results suggested that this newly established approach could be used to rapidly evaluate the quality of herbs from different origin, and to provide good strategy for further rectify and standardize the herb market. Copyright © 2013 John Wiley & Sons, Ltd.